Electromagnetic waves in a model with Chern-Simons potential - Pis'mak, Dar'ya Yur'evna; Pis'mak, Yury Mikhailivich; Wegner, Franz (Physical review. E, Statistical, nonlinear, and soft matter physics, 2015)
We investigated the appearance of Chern-Simons terms in electrodynamics at the surface or interface of materials. The requirement of locality, gauge invariance, and renormalizability in this model is imposed. Scattering and reflection of electromagnetic waves in three different homogeneous layers of media is determined. Snell's law is preserved. However, the transmission and reflection coefficient depend on the strength of the Chern-Simons interaction (connected with Hall conductance), and parallel and perpendicular components are mixed.